(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: A clinico-epidemiological study was conducted at two veterinary hospitals in Dhaka to evaluate the prevalence of parvoviral enteritis (PVE) in dogs and feline panleukopenia (FPL) in cats, to detect factors associated with them, and to identify their common clinical signs. Materials and Methods: Clinico-epidemiological data were collected for a total of 88 dogs and 129 cats which were presented to the hospitals, entered into MS excel 2010, and then transferred to STATA-14 software for conducting descriptive and univariable statistical analyses (Fisher’s exact test). The maps showing the spatial distribution of PVE and FPL were produced by using QGIS software version 2.18.13. Results: PVE in dogs and FPL in cats had the highest prevalence compared to other diseases (34.1%; 95% confidence interval: 24.3–44.9; N = 88 and 20.2%; 95% confidence interval: 13.6– 28.1; N = 129, respectively). Young age (43.8%), poor body condition (58.4%), and exotic breeds (44.2%) were significantly associated with the occurrence of PVE (p ≤ 0.05). Poor body condition (27.8%) and non-vaccination status (26.7%) were associated with FPL (p ≤ 0.05). Both PVE and FPL showed clinical signs of being off-feed, frequent vomiting, weakness, and moderate dehydration. Conclusion: The high prevalence of PVE and FPL indicates that they are common in dogs and cats in Dhaka, Bangladesh. The factors related to PVE are young age, exotic breed, and poor body condition score (BCS), and FPL are poor BCS and non-vaccination. Specific measures such as care during younger age, good nutrition, and routine vaccination are needed to prevent and control PVE and FPL in Dhaka’s dog and cat population. J. Adv. Vet. Anim. Res., 7(4): 726-733, Dec 2020 http://doi.org/10.5455/javar.2020.g474